Rancang Bangun Sistem Informasi Penentuan Harga Pokok Produksi Dan Harga Standar Pada Cv.Anugerah Mulya Rejeki - Setiawan, Stanly Dody; Widodo, Arifin Puji; Sukmaaji, Anjik (Jurnal JSIKA, 2012)
“In the production process orders every type of product produced or require treatment to its own peculiarities of each product use different resources. CV. Anugerah is one of the companies that manufacture a product based on orders from customers. Companies have difficulty in determining the sale price because the owner determines based on the selling price before to the determination of the selling price could be too high and too low, this could result in losses for the company. By information technology, the company needs the cost of production information systems based on standard cost which can take into account raw material costs, labor costs and factory overhead costs that can be used as a basis in the sale price. Application of information systems can be used for the calculation of cost basis for setting standards in product selling prices, the actual cost of production, gross profit based on selling price of the standard and actual prices. Implementation and evaluation of processes, information systems are made to calculate and display Standard Cost, selling price, the actual cost price, gross profit and displays a comparison report to see the difference of each component of the cost of production.” Keywords : Cost Of  Production, Standard Cost, Selling Price.